Using Problem-Solving Methods to Improve Mathematics Learning Achievement for Primary School Students - Rong, Wang; Wimuttipanya, Jittawisut (Asia Social Issues, 2025)
This study investigates the effectiveness of the problem-solving method in enhancing mathematics performance among fourth-grade primary school students in Shanghai. Integrating quantitative and qualitative research methods offers a nuanced understanding of the methodology’s impact on student learning. Utilizing a rigorous mixed-methods approach, the study meticulously develops a problem-solving model grounded in the latest curriculum standards, ensuring its alignment with contemporary educational objectives. The study quantitatively and qualitatively assesses the impact of this methodology. With 80 students, including 20 in an experimental group, pre-tests and post-tests show that the method significantly stimulates learning interest, promotes logical thinking, and improves mathematics performance. Notably, the qualitative data illustrates how problem-solving pedagogy can be helpful and understandable in the primary maths classroom, revealing a shift from passive learning to active engagement.In conclusion, this study provides new perspectives and effective strategies to enhance primary school students’ learning ability in mathematics, which has important theoretical and practical significance.